The influence of speed and power load on the indicators of the distribution of attention of schoolchildren with different typologies (Bangladesh Journal of Medical Science, 2022)
Objective: is to determine the effect of speed and strength training on the indicators of attention distribution in children aged 13-14 years, taking into account the strength of their nervous system.Method: the pedagogical experiment took place in an ordinary school in the city of Kirov for three months. Schoolchildren were engaged in physical education twice a week for 40 minutes each lesson. 20 schoolchildren from class 7a were engaged in the usual physical education program. Schoolchildren from the 7b class in the number of 20 people additionally performed a set of exercises in physical education lessons aimed at developing speed and strength abilities. The tapping test differentiated the schoolchildren into two subgroups according to the strength of the nervous system. Indicators of the distribution of attention of schoolchildren were determined by the testResults: after the end of the study, there were changes in all subgroups. In the group of class 7a, children with a strong nervous system improved from 27.3±1.5 seconds to 25.9±1.4 seconds (5%), and children with a weak nervous system improved from 29.0±3.2 seconds to 27.3±3.0 seconds (6%). In the group of children of class 7b, there were more significant changes. In schoolchildren with a strong nervous system, the indicators improved from 31.4±2.9 seconds to 25.4±2.3 seconds (19%), and in children with a strong nervous system, the indicators became higher from 30.3±2.2 seconds to 25.1±1.8 seconds (17%).Conclusion: the indicators of the distribution of attention of schoolchildren will improve if they perform physical exercises at each lesson in physical culture, which are aimed at the development of speed and strength abilities. The load should be differentiated taking into account the strength of the nervous system of schoolchildren.Bangladesh Journal of Medical Science Vol. 21 No. 03 July’22 Page: 634-638